Pertinencia de la asignatura de fotografía en el perfil del comunicador - Bajaña Alarcón, Nayeli Denys (2023)
The general objective of this case study is to analyze the relevance of the subject of photography in the profile of the communicator, in order to determine their importance and contribution in skill development and competencies necessary for professional practice in the field of communication. For its success, descriptive research is proposed, using both qualitative and quantitative approaches to get a broad view of the problem and the respective data collection. The study group or population is centered on students and teachers in the area of communication at the Technical University of Babahoyo, and information will also be obtained through qualitative techniques applied to professionals working in the province of Los Ríos. Interviews, surveys and an exhaustive bibliographic review will be applied in order to know opinions, experiences, suggestions of the characters of the subject. The aim is to obtain results that contribute and evidence the importance of photography and its relevance nowadays, as well as to contribute to the improvement of the subject, propose strategies for the formation and competences of communicators.